Constrained collective self-assembly model based on collision delay strategy - Quan-sheng DOU; Wen AN; Ping JIANG; Zhong-zhi SHI (Tongxin xuebao)
The collective self-assembly problem on two dimensional grid space were studied,and put forward sufficient and necessary condition for ensuring the connectivity of the assembly structure side,w ich was proved strictly.Based on this condition,parallel assembly strategy was proposed for collective self-assembly model based on maximum adjacent side closing and collision delay.Under the parallel condition,the model could assembly arbitrary side connective structure on two dimensional grid space,and through simulation some properties of the model were analyzed and proved further.